2014
DOI: 10.1186/1745-6150-9-14
|View full text |Cite
|
Sign up to set email alerts
|

Midichlorians - the biomeme hypothesis: is there a microbial component to religious rituals?

Abstract: BackgroundCutting edge research of human microbiome diversity has led to the development of the microbiome-gut-brain axis concept, based on the idea that gut microbes may have an impact on the behavior of their human hosts. Many examples of behavior-altering parasites are known to affect members of the animal kingdom. Some prominent examples include Ophiocordyceps unilateralis (fungi), Toxoplasma gondii (protista), Wolbachia (bacteria), Glyptapanteles sp. (arthropoda), Spinochordodes tellinii (nematomorpha) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Originally they propose (highlights in bold by PS): "We hypothesize that certain aspects of religious behavior observed in the human society could be influenced by microbial host control and that the transmission of some religious rituals could be regarded as the simultaneous transmission of both ideas (memes) and parasitic organism." [6]. Theoretically, this statement can be falsified under either of two conditions:…”
Section: Unfalsifiability Of the Biomeme Hypothesismentioning
confidence: 98%
See 2 more Smart Citations
“…Originally they propose (highlights in bold by PS): "We hypothesize that certain aspects of religious behavior observed in the human society could be influenced by microbial host control and that the transmission of some religious rituals could be regarded as the simultaneous transmission of both ideas (memes) and parasitic organism." [6]. Theoretically, this statement can be falsified under either of two conditions:…”
Section: Unfalsifiability Of the Biomeme Hypothesismentioning
confidence: 98%
“…A substantial body of sociological research suggests that religious beliefs are associated with better mental health as indicated by satisfaction with life, better mood, feeling of happiness, less depression, and less addiction among believers compared to non-believers [13][14][15]. Regarding this, Panchin et al should be extremely cautious when assigning rational meaning to religious rituals as useless activities without obvious benefits [6].…”
Section: Unfalsifiability Of the Biomeme Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis of Panchin et al certainly does not pass Popper’s test. Originally they propose (highlights in bold by PS): “ We hypothesize that certain aspects of religious behavior observed in the human society could be influenced by microbial host control and that the transmission of some religious rituals could be regarded as the simultaneous transmission of both ideas (memes) and parasitic organism.” [ 6 ]. Theoretically, this statement can be falsified under either of two conditions: The known microbes incline people to participate in some undefined religious rituals; Unknown microbes incline people to participate in given religious rituals.…”
Section: Unfalsifiability Of the Biomeme Hypothesismentioning
confidence: 99%
“…Today, using large quantitative data sets from hundreds of genomic and proteomic screens available in open access databases, scientists can generate a variety of novel hypotheses and full-fledged theories without even running “wet” experiments [ 1 - 5 ]. In line with this scientific paradigm, Panchin et al [ 6 ] posed an interesting question: what if some microbes might subtly manipulate human brain toward certain religious rituals that are beneficial for the propagation of the given microbe(s). They called it the “biomeme hypothesis”.…”
Section: Introductionmentioning
confidence: 99%